ROTOR INERTIA SYMMETRY (DESIGN BALANCE) PROJECT SUPPORT - Oleg O. Polushkin (Advanced Engineering Research)
Analysis problems of rotor imbalance from its peripheral working parts (hummers, knives, etc.) installation and the specified synthesis of its inertia symmetrical (balanced) structure are considered and formalized for the computing.